Human Resource Transformation of the Merah Putih Cooperative in Sinjai Regency - Tuti Supatminingsih; Andi Asti Handayani; Kartika Septiary Pratiwi Musa (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Human resource (HR) transformation is a major challenge in developing the Merah Putih Cooperative in Sinjai Regency, particularly in responding to digitalization and strengthening cooperative institutions. Low digital literacy, limited managerial capability, weak innovation culture, and slow leadership regeneration have hindered the cooperative’s optimal development. This study aims to analyze the condition of HR transformation, identify the challenges faced by the cooperative, and formulate strategies for strengthening HR at the Merah Putih Cooperative in Sinjai Regency. A qualitative approach with a case study design was employed. Research informants consisted of cooperative administrators, cooperative members, cooperative assistants, and representatives of the Sinjai Regency Cooperative and MSME Office. Data were collected through in-depth interviews, observation, documentation, and Focus Group Discussions (FGDs), and were analyzed using the Miles, Huberman, and Saldaña model. The findings indicate that cooperative HR transformation has not yet been implemented optimally. Most cooperatives continue to rely on manual administrative systems and have limited digital capability. However, some cooperatives have begun to transform through digital training, social media use, and collaboration with universities. The study also found that transformational leadership and member participation are important factors supporting successful cooperative transformation. The study concludes that strengthening digital competence, adaptive organizational culture, and innovative leadership is essential for developing modern and competitive cooperatives. Its implications emphasize the need for sustainable training programs and multi-stakeholder collaboration to support cooperative HR development.